Research on coal demand forecast and carbon emission reduction in Shanxi Province under the vision of carbon peak - Hu, Yanyong; Zhang, Rui; Qie, Xiaotong; Zhang, Xiaoyi (Frontiers in Environmental Science, 2022)
Accurately predicting the future demand quantity and changing the trends of coal resources is the key to maintaining national energy security and achieving the goal of “carbon peak and carbon neutrality.” To improve the prediction accuracy, this study sorts out eight common factors affecting the coal demand from the aspects of the economy, population, and energy. The grey correlation analysis method was used to describe the degree of importance of each factor and screen out the relatively vital factors. The system dynamics model for coal demand in Shanxi Province was also established. The coal demand and carbon emission trends in Shanxi Province from 2021 to 2030 were predicted under business-as-usual, low-speed and high-speed development scenarios. The study results show that: (1) During the 14th Five-Year Plan to 15th Five-year Plan, the trend of coal demand has changed from increasing to decreasing. The coal demand will reach its peak in 2025 and will reach 394.767 million tons, 390.273 million tons, and 385.658 million tons under the three scenarios, respectively. (2) With the development of population and economy, the total energy demand shows a continuously increasing trend. It is estimated that the total energy consumption will reach 237.4570-242.931 million tons of standard coal in 2030, and the total energy demand will continue to grow in the foreseeable future. (3) The carbon dioxide emission is closely related to the coal demand, showing a similar variation trend. Under the business-as-usual development scenario, carbon emissions are expected to reach 681.1248 million tons in 2030. The low-speed development and high-speed development scenarios have different degrees of energy saving and emission reduction benefits. Compared with the business-as-usual development scenario in 2030, the carbon dioxide emissions will be reduced by 1.6412 million tons and 3.5607 million tons respectively.